Đáp án:1260
Giải thích các bước giải:
$\begin{array}{l}
{\left( {x + y - z} \right)^9} = \sum\limits_{k = 0}^9 {C_9^k.{{\left( {x + y} \right)}^{9 - k}}.{{\left( { - z} \right)}^k}} \\
khi\,{z^4} \Rightarrow k = 4 \Rightarrow bt:C_9^4.{\left( {x + y} \right)^5}.{z^4} = C_9^4.{z^4}.\sum\limits_{k = 0}^5 {C_5^k} .{x^{5 - k}}.{y^k}\\
khi\,{x^2}.{y^3} \Rightarrow k = 3\\
\Rightarrow so\,hang\,chua\,\,{x^2}.{y^3}.{z^4}la:\,C_9^4.{z^4}.C_5^3.{x^2}.{y^3} = C_9^4.C_5^3.{x^2}.{y^3}.{z^4} = 1260.{x^2}.{y^3}.{z^4}\\
he\,so\,{x^2}.{y^3}.{z^4}la:1260
\end{array}$